Common volume coherent and incoherent scatter radar observations of mid-latitude sporadic E-layers and QP echoes - D. L. Hysell; M. F. Larsen; Q. H. Zhou (Annales Geophysicae, 2004)
Common-volume observations of sporadic E-layers made on 14-15 June 2002 with the Arecibo incoherent scatter radar and a 30MHz coherent scatter radar imager located on St. Croix are described. Operating in dual-beam mode, the Arecibo radar detected a slowly descending sporadic E-layer accompanied by a series of dense E-region plasma clouds at a time when the coherent scatter radar was detecting quasi-periodic (QP) echoes. Using coherent radar imaging, we collocate the sources of the coherent scatter with the plasma clouds observed by Arecibo. In addition to patchy, polarized scattering regions drifting through the radar illuminated volume, which have been observed in previous imaging experiments, the 30MHz radar also detected large-scale electrostatic waves in the E-region over Puerto Rico, with a wavelength of about 30km and a period of about 10min, propagating to the southwest. Both the intensity and the Doppler shifts of the coherent echoes were modulated by the wave.